Facilitating Veteran Student Success: Experiences from an Accelerated BS Program - Roberta Anne Rolland; Alicia Gill Rossiter; Dianne Morrison-Beedy (The Ohio State University Libraries, 2023)
Background: Military Veterans (MVs) face unique challenges that are important to recognize when building supportive academic environments. There is a need to broaden our understanding of the diverse student population within academia, requiring us to hear their voices and deduce facilitators and barriers to their academic transition and success. Aim: The aim of this study was to explore the unique needs of MV students and understand obstacles and facilitators for successful transition and completion for MV students entering a civilian baccalaureate program. Method: This study was guided by a phenomenological approach; we conducted three focus group interviews with Veteran students (n = 17) and conducted verbatim transcription thematic analysis. Results: Three themes were identified that impacted student success: (1) military experience prepared me for academic challenges, (2) defining my new role, and (3) no one left behind. Specific exemplars for thematic components to support transitioning into a civilian academic program included incorporating a military liaison for academic guidance and mentoring, acknowledging baseline skills using competency-based cohorts, and facilitating opportunities for connecting with other Veterans. Conclusion: Preparation of faculty and staff to better understand MV's specific needs in civilian academic environments is needed.